2014
DOI: 10.1016/j.annemergmed.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A Text Message Alcohol Intervention for Young Adult Emergency Department Patients: A Randomized Clinical Trial

Abstract: Objective Opportunistic brief in-person Emergency Department (ED) interventions can be effective at reducing hazardous alcohol use in young adult drinkers, but require resources frequently unavailable. Mobile phone text messaging (SMS) could sustainably deliver behavioral support to young adult patients, but efficacy remains unknown. We report 3-month outcome data of a randomized controlled trial testing a novel SMS-delivered intervention in hazardous drinking young adults. Methods We randomized 765 young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
197
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(201 citation statements)
references
References 44 publications
2
197
1
1
Order By: Relevance
“…Several recent studies have shown that mobile phone‐delivered interventions have the potential to influence drinking behaviour in emergency department attendees 16, 17, 18, college students 19, 20, young people 21, adults 22 and alcohol‐dependent patients 23. Delivering an alcohol brief intervention by mobile phone would be ideal for targeting disadvantaged groups who may be reluctant to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that mobile phone‐delivered interventions have the potential to influence drinking behaviour in emergency department attendees 16, 17, 18, college students 19, 20, young people 21, adults 22 and alcohol‐dependent patients 23. Delivering an alcohol brief intervention by mobile phone would be ideal for targeting disadvantaged groups who may be reluctant to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…Tailored advice was sent to participants based on their responses. The authors found small reductions in their intervention group's self-reported drinks per day and number of drinking days, compared to the control group [9].…”
Section: Introductionmentioning
confidence: 88%
“…They found that the intervention group consumed fewer drinks per drinking day in the last month at follow-up, compared to controls. In a subsequent study they expanded on this method by asking young people to report their intentions to drink on the coming weekend, commitment to reduce drinking, and later, their actual weekly drinking [9]. Tailored advice was sent to participants based on their responses.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to date on the effectiveness of alcohol brief interventions comes from general population studies primarily in primary healthcare settings 18 19. However, results may be different for military personnel who have different pressures and demands.…”
Section: Introductionmentioning
confidence: 99%